2021
DOI: 10.1055/s-0041-1729939
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação das concordâncias intra e interobservadores da nova classificação AO/OTA para fraturas da região trocantérica e do colo do fêmur

Abstract: Resumo Objetivo Neste estudo, investigamos a concordância intra e inter-observador da nova classificação Arbeitsgemeinschaft für Osteosynthesefragen/Orthopaedic Trauma Association (AO/OTA) para fraturas da extremidade proximal do fêmur. Métodos Foram selecionadas 100 radiografias do quadril de pacientes que sofreram fraturas da região trocantérica ou do colo do fêmur. Quatro ortopedistas cirurgiões de quadril e quatro residentes de ortopedia e traumatologia avaliaram e classificaram as frat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…However, prior studies have demonstrated only moderate interobserver agreement on 31-A3 subgroups, with Kappa generally in the fair range. 24 25) Despite attempts to refine the system, variability in radiographic interpretation remains. While we used an experienced surgeon reader, fracture classification reliability was a limitation without multiple blinded observers.…”
Section: Discussionmentioning
confidence: 99%
“…However, prior studies have demonstrated only moderate interobserver agreement on 31-A3 subgroups, with Kappa generally in the fair range. 24 25) Despite attempts to refine the system, variability in radiographic interpretation remains. While we used an experienced surgeon reader, fracture classification reliability was a limitation without multiple blinded observers.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, like the Gustilo-Anderson classification system, 2 other groups have criticized the OTA-OFC as only exhibiting moderate interobserver grading agreement, particularly among junior surgeons. 3,4 It also remains unclear which OTA-OFC categories overlap with the Gustilo-Anderson classification or add unique value for clinical decision making.…”
Section: Introductionmentioning
confidence: 99%
“…Today, orthopedic surgeons must be aware of 3D-CT, based on the analysis of three-dimensional fragments, for a better classification of fractures of the proximal femur since it better evaluates fragmentation and instability and has better interobserver and interobserver reliability than conventional twodimensional systems, even for AO/OTA classification [20]. The current version, revised in 2018, has provided acceptable reliability in the diagnosis of femoral trochanteric fractures; with the addition of 3D-CT, it will increase.…”
mentioning
confidence: 99%
“…The current version, revised in 2018, has provided acceptable reliability in the diagnosis of femoral trochanteric fractures; with the addition of 3D-CT, it will increase. If we do not have 3D tomography equipment in our hospital, the current AO/OTA classification of intertrochanteric fractures should be used in some way, using the three main types, because this allows a common language among treating physicians [18][19][20].…”
mentioning
confidence: 99%